1958
DOI: 10.1084/jem.107.2.291
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Pathogenesis of Fever

Abstract: By means of a method designed to compare the febrile responses produced by intracarotid and intravenous injections, the endogenous pyrogen, which is contained in leucocytic exudates and is present in the serum of rabbits 2 hours after intravenous injections of typhoid vaccine, has been shown to act directly upon the thermoregulatory centers of the brain. In contrast, the exogenous bacterial pyrogen present in serum obtained 5 minutes after vaccine injections was found to act by a different and less direct mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1958
1958
1978
1978

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(14 citation statements)
references
References 17 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…The release of endogenous pyrogen in the donor animal given virus is not associated with the characteristic changes in circulating polymorphonuclear leukocytes (initial leukopenia followed by leukocytosis) which occur when either bacterial or tissue polysaccharides are injected (1,39). Further evidence for the dissimilarity between these substances and endogenous pyrogen obtained in other types of experimental fever is presented elsewhere (8,27,30,(40)(41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The release of endogenous pyrogen in the donor animal given virus is not associated with the characteristic changes in circulating polymorphonuclear leukocytes (initial leukopenia followed by leukocytosis) which occur when either bacterial or tissue polysaccharides are injected (1,39). Further evidence for the dissimilarity between these substances and endogenous pyrogen obtained in other types of experimental fever is presented elsewhere (8,27,30,(40)(41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 90%
“…It is the circulation of this latter substance which, in turn, is believed to be responsible for the development of fever. The rapid onset of fever following injection of viral-induced endogenous pyrogen further suggests that this material like other endogeneous pyrogens acts directly on the thermoregulatory centers of the brain (42). SUMMARY A substance with pyrogenic properties appears in the blood streams of rabbits made febrile by the intravenous inoculation of the PR8 strain of influenza A and Newcastle disease viruses (NDV).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, when bacterial endotoxin is incubated with polymorphonuclear leucocytes in vitro, the endotoxin is inactivated, and the endogenous pyrogen is released from the leucocytes (17). Finally, there is indirect evidence that leucocytic and endogenous pyrogens act upon the thermoregulatory centers of the brain (14). Despite the foregoing evidence, the observations of Bennett, Petersdorf, and Keene (5) are frequently cited as contradicting the endogenous pyrogen hypothesis (5-13).…”
Section: Comparative Concentrations Of Transferable Pyrogen In Sera Omentioning
confidence: 63%
“…The presence of an endogenous pyrogen in the blood of normal animals given endotoxin intravenously (13)(14)(15), differing in properties and action from the exogenous pyrogen (9,16,35), is well established. The recognition of the polymorphonuclear leucocyte as the source of serum pyrogen is equally well established: leucocytic pyrogen (18,(20)(21)(22) appears to be identical with the circulating endogenous pyrogen, and animals made severely leucopenic by treatment with a nitrogen mustard prior to injection of endotoxin lack endogenous pyrogen (24,25).…”
Section: Tolerance To Pyrogenicit¥mentioning
confidence: 99%
“…Following the demonstration by Grant and Whalen (13) of an endogenous pyrogen in the blood of rabbits injected with typhoid vaccine, an impressive series of experiments by Wood and coworkers (14)(15)(16)(17) has led to the hypothesis that endotoxininduced fever is a consequence of the action of the exogenous pyrogen upon the leucocytes, or other cells, causing release of endogenous pyrogen which then acts upon the thermoregulatory centers of the brain (4). From an equally impressive series of researches, Bennett and associates (9,(18)(19)(20)(21)(22)(23)(24)(25) have shown that the fever seen after administration of endotoxin requires neither significant numbers of circulating leucocytes nor the presence of endogenous serum pyrogen, and have postulated a dual mechanism, involving a direct action of endotoxin, possibly accounting for the biphasic nature of the febrile response (3).…”
mentioning
confidence: 99%